2011
DOI: 10.3923/ijps.2011.176.184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Organic Acids on Performance, Nutrients Digestibility and Health of Broiler Chicks

Abstract: This study was conducted to compare the effects of different types and levels of organic acids being Formic (0.25, 0.5 and 1.0% FA), Fumaric (0.5, 1.0 and 1.5% FUA), Acetic (0.25, 0.50 and 0.75% AC) and Citric Acids (1, 2 and 3% CA). A total number of 351 one d-old Arbor-Acres broiler chicks were randomly divided into 13 treatment groups, each in three replicates of 9 chicks per replicate. The first group was fed the basal diet without supplementation and served as control. While, the other groups were receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
63
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 21 publications
13
63
2
5
Order By: Relevance
“…Several studies have demonstrated the importance of organic acids such as humic acid in the immune response of birds. Abdel-Fattah et al (2008), Ghazala et al (2011), andHoushmand et al (2012) observed that birds fed an organic acid-supplemented diet had heavier immune organs (bursa of Fabricius and the thymus) and a higher level of globulin in their serum, which is an indicator of immune response. Although broiler chickens in the control had some reduction in thymic volume units and the follicles of the bursa of Fabricius, this was not a manifestation of lymphocytic depletion of the thymus and bursa of Fabricius.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the importance of organic acids such as humic acid in the immune response of birds. Abdel-Fattah et al (2008), Ghazala et al (2011), andHoushmand et al (2012) observed that birds fed an organic acid-supplemented diet had heavier immune organs (bursa of Fabricius and the thymus) and a higher level of globulin in their serum, which is an indicator of immune response. Although broiler chickens in the control had some reduction in thymic volume units and the follicles of the bursa of Fabricius, this was not a manifestation of lymphocytic depletion of the thymus and bursa of Fabricius.…”
Section: Discussionmentioning
confidence: 99%
“…Increased permeability allows easier assimilation of minerals from the gut and their transfer from blood to the bone and cells, resulting in effective bone development (Stepchenko et al, 1991;Dinev, 2012). Like other organic acids, humic acid may play a significant role in the development of immune organs, particularly the bursa of Fabricius and thymus, which are the major components of the avian immune system (Abdel-Fattah et al, 2008;Ghazala et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There was significant increase in CD4 and TCR-II cells in the 0.1% Vitamin C group as compared with control and these cells participate in the immune response to the exogenous antigen, stimulating the synthesis of Interleukin-2, which activates CD8, natural killer (NK) cells and B cells. In a study by Ghazala et al (2011) birds fed an organic acid supplemented diet had heavier immune organs (bursa of Fabricius and the thymus) and higher level of globulin in their serum as well. Houshmand et al (2012) found that dietary addition of organic acids resulted in significant increases in antibody titres against Newcastle disease in broilers.…”
Section: Effect Of Organic Acid On Broiler Performancementioning
confidence: 98%
“…Hashemi et al (2014) added an acidifier mixture (formic, phosphoric, lactic, tartaric, citric and malic acids) in the broiler diet at the rate of 0.15% and reported increased body weight gain in organic acid supplemented group. Such a positive impact of dietary acidifiers on growth performance might be due to a reduction of pH values in the feed and digestive tract, killing the pathogenic organisms which are sensitive to low pH or selectively increasing the acid loving lactobacillus and a direct antimicrobial effect (Ghazala et al, 2011). A survey was conducted by Kim et al (2015) of 31 recent publications and compared the effects of diets on body weight gain, feed intake, and feed efficiency (gain to feed ratio) with those of control diets (Table 3).…”
Section: Effect Of Organic Acid On Broiler Performancementioning
confidence: 99%
See 1 more Smart Citation